Identitas Visual Milenial Dalam Merek Minuman Bubble Tea di Tangerang Selatan - Arief Ruslan (Avant Garde, 2020)
This article investigates the visual identity of “newest” soft drink businesses that target milennial communities in the South Tangerang region. The “kekinian” drinks, popular as millennial drinks and make this business blooming and compete with one another. Appending from some form of visual identity from within "branding" by business man, the discourse on milennial identity is indirectly built on several visual principles. Visual identity becomes the main channel as a communication tool and determines identity as social identity. This research focuses on "bubble drink" soft drink business people, or often called bobba drinks, who build their identity with logos as milennial identity. Using a qualitative method with observation and study of literature, this study took the visual identity (logoS) of 17 boba drink businesses in the South Tangerang area. With this logo, the researcher identifies the concept of communication in a visual form, which then unravels the signs that are present in the visual metaphore element, namely shape, color, and typography. The findings in this study are, a) The visual order presented by business people in building milennial children's identity is presented with flexible shapes, dominant colors that are contrast, and promotes the role of words combined with typographic forms. b) visual style that is built not only as a form of simplicity, but also as the identity “kekinian” society.